PENGARUH PERAN WHISTLEBLOWING SYSTEM DALAM PENEREAPAN DIGITALISASI DAN PENGAWASAN PAJAK TERHADAP KEPATUHAN WAJIB DI KANTOR DIREKTORAT JENDRAL PAJAK - Kumala, Ratih; Janah, Anis Miftahul (Jurnal Ilmu Administrasi Publik, 2025)
This study aims to determine the role of the whistleblowing system in implementing tax digitalization and supervising taxpayer compliance. This study uses a quantitative method. The population is taxpayers who have used the whistleblowing system website. The sampling technique is saturated samples or non-probability sampling, and 100 respondents were obtained. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple linear regression analysis. The hypothesis testing design used is the normality test, multicollinearity test, heteroscedasticity test, f-test, t-test, and coefficient of determination. Based on the results of the conducted tests, the following research findings emerged: 1) The whistleblowing system plays a positive and significant role in enhancing taxpayer compliance in the context of digitalization. 2) Tax supervision also has a positive and significant effect on taxpayer compliance. Based on the results of the tests conducted, the following research results were found: 1) the role of the whistleblowing system in the implementation of digitalization has a positive and significant effect on taxpayer compliance, 2) tax supervision has a positive and significant effect on taxpayer compliance